2016
DOI: 10.1186/s12906-016-1321-8
|View full text |Cite
|
Sign up to set email alerts
|

Zhengtian Capsule versus flunarizine in patients with migraine: a multi-center, double-blind, double-dummy, randomized controlled, non-inferior clinical trial

Abstract: BackgroundThe primary objective of this study was to assess whether Zhengtian Capsule was non-inferior to flunarizine in efficacy and safety profile for prevention of migraine in adults.MethodsThis was a double-dummy, double-blind, multicenter, positive drug (flunarizine), parallel randomized controlled, non-inferior clinical trial. Patients (n = 360) were randomized in a 1:1 to receive either Zhengtian Capsule or flunarizine, including 12 weeks’ intervention and 4 weeks’ follow-up. The primary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Currently, positive control is one of the most commonly used control methods in randomized controlled trials (RCTs). The calcium channel blocker flunarizine, recognized as a first-line treatment for migraine [ 22 25 ], is widely used as a comparator in RCTs [ 37 , 75 , 76 ]. This control design is a good way to compare the efficacy, tolerability, and safety of different medical interventions for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, positive control is one of the most commonly used control methods in randomized controlled trials (RCTs). The calcium channel blocker flunarizine, recognized as a first-line treatment for migraine [ 22 25 ], is widely used as a comparator in RCTs [ 37 , 75 , 76 ]. This control design is a good way to compare the efficacy, tolerability, and safety of different medical interventions for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to cause reversible fetal or neonatal bradycardia [79][80][81][82][83][84][85][86][87][88][89].…”
Section: Prophylaxis In Pregnant Patientsmentioning
confidence: 99%
“…Of note, the good safety of Zhengtian Capsule was evidenced by no severe adverse events that occurred in this study. However, patients who received flunarizine had trouble with body weight gain (Cao et al, 2016). Another trial recruiting 150 migraine sufferers reported that ChuanXiong Ding Tong herbal formula granule that possesses nine herbs like Chuanxiong Rhizoma, Cyathulae Radix, and Uncariae Ramulus Cum Uncis, was more effective than placebo in reducing migraine duration, frequency, visual analog scale score, and alleviating pain intensity for a treatment period of 16 weeks (Fu et al, 2012).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Zhengtian Capsule was evidenced by no severe adverse events that occurred in this study. However, patients who received flunarizine had trouble with body weight gain(Cao et al, 2016).…”
mentioning
confidence: 99%